Do or do not. Cognitive configurations affecting open innovation adoption in SMEs. (January 2023) - Marzi, Giacomo; Fakhar Manesh, Mohammad; Caputo, Andrea; Pellegrini, Massimiliano Matteo; Vlačić, Božidar
Abstract: The adoption of Open Innovation (OI) in small and medium-sized enterprises (SMEs) often rests on its positive evaluation from top-management teams and/or entrepreneurs. Because of the mixed outcomes attainable through SMEs' openness, managers must weigh the beneficial aspects of boundary-spanning against the complexities coming from inter-organizational arrangements and knowledge transfer. Building upon the tenets of dual-process theory, this study highlights the cognitive configurations leading toward willingness or reluctance of OI adoption in SMEs. This is done by investigating perceptions of barriers, benefits, and organisational resistance to openness, such as the not-invented-here (NIH) and not-shared-here (NSH) syndromes in combination with decision-makers' cognitive styles. To shed further light on observed heterogenous outcomes and the effects of managerial cognitive configurations, this study analyses the willingness and reluctance to adopt OI among 434 managers and entrepreneurs working in SMEs. The results of combined PLS-SEM and fsQCA analyses outline different decisional paths associated with willingness and reluctance to adopt OI. Thus, this research contributes to the 'human side of OI' paradigm by providing fruitful implications about cognitive configurations of decision-makers in SMEs concerning OI adoption. Highlights: This study shows the decision-making processes leading to the willingness or reluctance to adopt Open Innovation in SMEs. Managerial cognitive configurations play an active role when appraising Open Innovation adoption. We present different managerial decisional paths associated with willingness or reluctance to adopt Open Innovation in SMEs.